Roux-en-Y gastric bypass alters intestinal glucose transport in the obese Zucker rat - Meng, Qinghe; Culnan, Derek M.; Ahmed, Tamer; Sun, Mingjie; Cooney, Robert N. (Frontiers in Endocrinology, 2022)
The gastrointestinal tract plays a major role in regulating glucose homeostasis and gut endocrine function. The current study examines the effects of Roux-en-Y gastric bypass (RYGB) on intestinal GLP-1, glucose transporter expression and function in the obese Zucker rat (ZR). METHODS: Two groups of ZRs were studied: RYGB and sham surgery pair-fed (PF) fed rats. Body weight and food intake were measured daily. On post-operative day (POD) 21, an oral glucose test (OGT) was performed, basal and 30-minute plasma, portal venous glucose and glucagon-like peptide-1 (GLP-1) levels were measured. In separate ZRs, the biliopancreatic, Roux limb (Roux) and common channel (CC) intestinal segments were harvested on POD 21. RESULTS: Body weight was decreased in the RYGB group. Basal and 30-minute OGT plasma and portal glucose levels were decreased after RYGB. Basal plasma GLP-1 levels were similar, while a 4.5-fold increase in GLP-1 level was observed in 30-minute after RYGB (vs. PF). The increase in basal and 30-minute portal venous GLP-1 levels after RYGB were accompanied by increased mRNA expressions of proglucagon and PC 1/3, GPR119 protein in the Roux and CC segments. mRNA and protein levels of FFAR2/3 were increased in Roux segment. RYGB decreased brush border glucose transport, transporter proteins (SGLT1 and GLUT2) and mRNA levels of Tas1R1/Tas1R3 and α-gustducin in the Roux and CC segments. CONCLUSIONS: Reductions in intestinal glucose transport and enhanced post-prandial GLP-1 release were associated with increases in GRP119 and FFAR2/3 after RYGB in the ZR model. Post-RYGB reductions in the regulation of intestinal glucose transport and L cell receptors regulating GLP-1 secretion represent potential mechanisms for improved glycemic control.